"This experience changed my life": inspiring college students to pursue careers caring for persons living with dementia. Issue 2 (1st February 2021) - Hamilton, Gillian; Lowes, Susan; Hochstetler, Vicki; Pierson, Kristen; Volk, Kylee
ABSTRACT: The number of Americans with dementia is expected to triple in 30 years. A workforce prepared to care for those persons is critical. A unique course at Arizona State University was created to address that need. Students enrolled in a course with weekly lectures by professionals working in dementia care, and also visited a person living with dementia each week, journaling about their visits. Journals were analyzed to explore the evolution of student attitudes throughout the semester. The states of "Exploration, " "Letting Go, " and "Connection" are described, with examples of journal entries provided. The course was successful in inspiring students to see persons living with dementia as fellow humans deserving of respect with whom they could enjoy rewarding relationships. This experience may lead them to have a special interest in persons living with dementia throughout their careers. Collaboration to create a similar course is invited.